Budaya Menghafal Al-Qur’ān: Studi Living Qur’ān Masyarakat Benda Brebes Jawa Tengah - Agus Irfan (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2018)
One of the phenomena of “Living Qur’ān” found in Benda, Central Java is the tradition of memorizing the Qur’ān. This paper presents an elaboration of the question “how the contextualization step for the taḥfīẓ al-Qur’ān education as a solution for taḥfīẓ al-Qur’ān exist in Benda Bumiayu Brebes? As formulated in three Sub Question: 1. How the taḥfīẓ al-Qur’ān culture for Benda society can be construct as long time exist? 2. What factors that supported the taḥfīẓ al-Qur’ān culture exist ? 3. What factors that reduced the taḥfīẓ al-Qur’ān culture exist?This research is a descriptive qualitative nature, employing historical and sosiological approaches. The qualitative data are obtained through observation, interview and documentation. The data collected are then selected and arranged in a sequence with argumentative presentation.The result of this research reveal that Benda village is good known by Dā al- Qur’ān, because he has more than 7 (seven) Islamic Boarding School for memorizing Qur’ān. This village used to create memorizing Qur’ān culture for the society and arround him. This culture is effected by KH. Khalīl Ibn Maḥallī dan KH. Suḥaimi Ibn Abdul Ghānī, and in the second generation he has great memorizing culture. But in the third generation he gets bad value that less. As  observation data, a writter has seen some fundamen factors which influence reducing the taḥfiẓ al-Qur’ān culture in that village. So that needed the contextualization of taḥfīẓ al- Qur’ān education that switable with modernity.